Analysis and comprehensive evaluation of sustainable land use in China: Based on sustainable development goals framework. (10th August 2021) - Lu, Xinhai; Zhang, Yanwei; Lin, Chaoran; Wu, Feng
Abstract: Based on UN 2030 Sustainable Development Goals (SDGs), this study selects 43 indicators from three dimensions to construct an evaluation index system for sustainable land use (SLU). Thirty provincial administrative regions in China from 2002 to 2018 are chosen to comprise the study area. Real-coded accelerating genetic algorithm–projection pursuit techniques and an exploratory spatial data analysis model are used to study the spatiotemporal differences in the SLU levels of the provinces in China. Results show the following: (1) During the study period, the SLU level in China demonstrated an overall upward trend of fluctuations, along with obvious regional differences. (2) The spatial pattern of the SLU level in China was high in the eastern region and low in the western region in the east–west direction; for the north–south direction, an inverted U-shaped distribution was noted. (3) The main types of local spatial autocorrelation are H–H and L–L types, and both have evident spatial clustering characteristics. (4) The realization of Goal A is the main driving force for the improvement of the SLU level, whereas the failure to realize Goals B and C effectively is the main bottleneck in the improvement of the SLU level. Highlights: A new evaluation index system for SLU based on SDGs in China was established. Mathematical and spatial techniques are applied in research on SLU level. The SLU level in China has spatial–temporal difference. Policy suggestions for improving the SLU level by achieving SDGs were proposed.